Customers’ Behavioural Intention Towards Internet Banking Usage in Kathmandu Valley - Bhandari, Ankit (Quest Journal of Management and Social Sciences, 2026)
Background: The rapid advancement of information and communication technology has transformed the global banking industry. Internet banking has emerged as a significant innovation, enabling customers to conduct financial transactions conveniently without visiting physical bank branches. In developing countries like Nepal, the adoption of internet banking is increasing; however, usage remains relatively limited due to technological, infrastructural, and security-related concerns. Purpose: The main concern of my study is access to customers' intention towards internet banking. Internet banking Usage is still an issue because of its complexities in adopting it from the technical as well as security perspective. This objective of my study is to determine the customers' behavioral intention towards internet banking usage in Kathmandu Valley. Design/methodology /approach: Explanatory research design was adopted as the main research paradigm to discover reality. The Technological Acceptance Model is applied as a theory. The study area is Kathmandu Valley. The data was evaluated quantitatively by using both descriptive and inferential statistics. Questionnaire was designed to collect the data and were entered into a KOBO Toolbox. SEM was used to analyze the relationships from 379 responses. Findings: The findings of the study show that major challenges were found to be internet connection problems and heavy network traffic for operating internet banking during pandemic. Government provisions or polices for the high internet service in Nepal could be the solution. Similarly, Perceived Ease of Use and Perceived Usefulness play a significant role in the behavioral intention towards internet banking. This finding gives theoretical relevance in terms of Technology Acceptance Model. Conclusion: The scope and depth of this study are confined to internet banking users residing in Kathmandu Valley. Further studies should include other variables to better understand the underlying relationship between internet banking and its intention to use. Security and privacy issues can be explored further. Implication includes policy making that focuses on enhancing the internet banking experience further. Key words: Internet Banking, Customers, Banks, Kathmandu Valley, Financial Literacy